Mussel-mimicking sulfobetaine-based copolymer with metal tunable gelation, self-healing and antibacterial capability - Miroslav Mrlík; Mário Špírek; Jassim Al-Khori; Ali Abdulrahman Ahmad; Jaroslav Mosnaček; Mariam AlAli AlMaadeed; Peter Kasák (Arabian Journal of Chemistry, 2020)
In the present study, the sulfobetaine-based copolymer bearing a dopamine functionality showed gel formation adjusted by the application of metal salts for gelation and various values of pH. Normally, the liquid-like solution of the sulfobetaine-based copolymer and metal cross-linkers is transformed to a gel-like state upon increasing the pH values in the presence of Fe3+ and Ti3+. Metal-induced coordination is reversible by means of the application of EDTA as a chelating agent. In the case of Ag+ ions, the gel is formed through a redox process accompanied with the oxidative coupling of the dopamine moieties and Ag0 particle formation. Mussel-mimicking and metal-dependent viscoelastic properties were observed for Fe3+, Ti3+, and Ag+ cross-linking agents, with additionally enhanced self-healing behavior in comparison with the covalently cross-linked IO4− analogues. Antibacterial properties can be achieved both in solution and on the surface using the proper concentration of Ag+ ions used for gelation; thus, a tunable amount of the Ag0 particles are formed in the hydrogel. The cytotoxicity was elucidated by the both MTT assay on the NIH/3T3 fibroblast cell line and direct contact method using human dermal fibroblast cell (F121) and shows the non-toxic character of the synthesized copolymer. Keywords: Polysulfobetaine, Metal coordination, Antibacterial, Self-healing, Hydrogels, Catecholamine polymers